Serum Interleukin-6 and Adiponectin Levels in Patients with Active or Inactive Behcet's Disease - Etem, Arzu; Yildirmak, Sembol Turkmen; Onalan, Ebru Etem; Baran, Fehmi; Seval, Hatice; Koldas, Macir; Yenice, Necati (Ortadogu Ad Pres & Publ Co, 2010)
Objective: Behcet's disease (BD) is a chronic systemic inflammatory disease and its etiopathogenesis still remains unknown. Cytokines play a role in immune response and inflammatory reactions. The aim of this study is to determine the levels of proinflammatory cytokine interleukin-6 (IL-6) and anti-inflammatory cytokine adiponectin in the sera of patients with BD and to assess their importance as biological markers for disease activity. Material and Methods: Forty-four BD patients [19 males, 25 females, age: 35.65 +/- 10.84 yrs (mean +/- standart deviation) (SD)] and 25 healthy controls (10 males, 15 females, age: 29.80 +/- 8.20 yrs) were included in the study. Patients were divided into active or inactive groups according to their clinical and laboratory findings (active, n= 21; inactive, n= 23). We determined serum IL-6 levels using the chemiluminescence method, and serum adiponectin levels by ELISA method. Results were expressed as mean +/- standard error (SE). Results: Serum levels of IL-6 and adiponectin in BD patients (n= 44) (5.24 +/- 0.84 pg/mL; 22.31 +/- 1.71 mu g/mL, respectively) were similar to the control group (n= 25) (4.59 +/- 1.01 pg/mL; 21.68 +/- 1.91 mu/mL, respectively). No significant difference was found in IL-6 and adiponectin levels between the active (n= 21), inactive (n= 23) and control (n= 25) groups. Conclusion: In parallel with the presence of inflammation and increased CRP, erythrocyte sedimentation rate and white blood cell count, higher IL-6 and lower adiponectin levels were expected in active BD patients compared to the controls. However, they were found to be similar in all groups. We conclude that ongoing anti-inflammatory treatment should be taken into consideration while interpreting the cytokine levels in these patients.
Aktif ya da inaktif behçet hastali?i bulunan hastalarin serum interlökin-6 ve adiponektin seviyeleri
Keywords: Behcet's syndrome; adipokines; interleukin-6